INDONESIAN MINISTER AMONG THE HONORARY DEGREE RECIPIENTS AT THE 52nd USM CONVOCATION CEREMONY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 15 November 2015 – The Minister of Research, Technology and Higher Education of Indonesia, Professor Dr. H. Mohamad Nasir and the Chairman of K.L.E. Society India, Dr. Prabhakar Basaprabhu Kore are among the recipients of the Honorary Doctor of Education degree in conjunction with the 52 Universiti Sains Malaysia (USM) Convocation ceremony which will commence on Tuesday.